Gonadotropin - Vizcarra, Jorge (IntechOpen, 2013)
This is a must-have book for those interested in reproduction. It provides a full account of our current knowledge of the hormones intimately associated with testicular and ovarian function. Each chapter is carefully organized to cover basic concepts and recent advances in gonadotropin synthesis and secretion. The information is presented in a sequence that provides researchers, teachers, and students with a logical integration of the reproductive axis. Practical applications associated with reproductive management of domestic species are also provided. Taken together, this book is a comprehensive combination of fundamental endocrine concepts and original findings in the area of gonadotropin function.